Factors affecting the risk appetite for supervisory boards - Jasiński, Bartosz (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
One of the important concepts building the foundations of risk management processes in a corporation is its risk appetite. At the supervisory board level, it is understood as the scope of risk that an organization is able to accept by building value for stakeholders. Due to the fact that the council represents key interest groups, directing activities related to it, active discussion, aimed at jointly determining its level. The purpose of the article is to attempt to indicate a set of functions that may have a significant impact on the level of additional equipment. Their knowledge can contribute to a better understanding of the corporate risk philosophy.